The "fuzzy front end" of product development: An exploratory study of German and Japanese innovation projects - Cornelius Herstatt; Birgit Verworn; Akio Nagahira (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2002)
In this paper, we report the complete and unabridged results of an exploratory study of typical front-end activities in 28 innovation projects in German and Japanese companies. We further reveal differences in the practice of innovation management in both countries. Based on these, we develop first evidence for effects of front end management practices on project execution and project outcomes. For this purpose, we interviewed managers of 13 Japanese and 14 German enterprises concerning 14 Japanese and 14 German new product development projects. The focus of the interviews was the so-called fuzzy front end and activities or deliverables later in the process which might be affected by front end management practice. Overall, most projects achieved their objectives with varying efficiency, which is therefore the focus of our analysis. Our study reveals similarities as well as distinctive differences between the projects studied in Japan and Germany. In sum, the 14 Japanese projects relied on a thorough planning and strict controlling to minimize deviations from front end specifications and enhance efficiency. The majority of the 14 German projects did not have a formal planning and controlling process supported by methods and tools like the Japanese projects. Instead, they integrated all relevant functions early in the process, partly already during idea generation, to ensure that all information and points of view were taken into consideration right from the start to reduce later deviations and enhance efficiency. Responsibilities were assigned during the front end and rarely changed during project execution. In addition, during the front end of the German and Japanese projects, market and technical uncertainty were strongly reduced prior to development to avoid later deviations and secure efficiency targets.
urn:nbn:de:gbv:830-opus-1471
Keywords: 650; Fuzzy front end; idea generation; project selection; project planning; Japan; Germany